Response, Adaptation and Mechanism of Wheat Plants to Salinity Stress - Pinem, Iwan; Nurhayati, Nurhayati; Sri Hafnida Ritonga; Aditya Sari, Ruri (Demeter: Journal of Farming and Agriculture, 2024)
Soil salinity has emerged as a major constraint to global food production, with its severity continuously escalating due to anthropogenic activities such as excessive irrigation, land degradation, and climate change. Wheat (Triticum aestivum L.), a staple crop and primary source of carbohydrates and energy for much of the global population, is particularly sensitive to salinity stress. High salt concentrations adversely affect the plant’s physiological and biochemical processes, including inhibited seed germination, stunted vegetative growth, disrupted reproductive development, reduced enzymatic activity, and impaired photosynthesis. Salinity stress also causes hormonal imbalances, induces oxidative stress through the accumulation of reactive oxygen species (ROS), and ultimately leads to significant yield losses. A comprehensive understanding of wheat’s responses to salinity stress is essential for developing effective mitigation strategies. Efforts to enhance salinity tolerance have included the selection of tolerant genotypes, conventional breeding programs, and molecular approaches such as genetic engineering. While promising, these methods are often time-consuming, costly, and labor-intensive. As a complementary solution, agronomic management practices have gained attention for their practical application in improving wheat performance under saline conditions. Techniques such as the use of arbuscular mycorrhizal fungi, plant growth-promoting rhizobacteria (PGPR), exogenous phytohormone application, seed priming, and proper nutrient management have shown effectiveness in enhancing plant resilience and productivity in saline soils. This paper reviews the physiological impacts of salinity on wheat, explores potential adaptive mechanisms, and discusses practical management strategies aimed at improving wheat performance under salt stress conditions.